2013
DOI: 10.1071/wf11179
|View full text |Cite
|
Sign up to set email alerts
|

Using native annual plants to restore post-fire habitats in western North America

Abstract: Increasing fire frequencies and uncharacteristic severe fires have created a need for improved restoration methods across rangelands in western North America. Traditional restoration seed mixtures of native perennial mid- to late-seral plant species may not be suitable for intensely burned sites that have been returned to an early-seral condition. Under such conditions, native annual plant species are likely to be more successful at becoming established and competing with exotic annual plant species, such as B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Limiting similarity theory predicts that plant communities are able to better resist invasion when resident species are more similar to potential invaders (Emery 2007). Our data also support recent evidence that early successional forbs can be successful as seeded species in preventing exotic invasions (Abella et al 2012;Herron et al 2013). Moreover, propagule supply for the tall annual exotic group of species was probably relatively low in the study area prior to cutting.…”
Section: Discussionsupporting
confidence: 86%
“…Limiting similarity theory predicts that plant communities are able to better resist invasion when resident species are more similar to potential invaders (Emery 2007). Our data also support recent evidence that early successional forbs can be successful as seeded species in preventing exotic invasions (Abella et al 2012;Herron et al 2013). Moreover, propagule supply for the tall annual exotic group of species was probably relatively low in the study area prior to cutting.…”
Section: Discussionsupporting
confidence: 86%
“…The small number of studies we identified and the diverse methods and metrics used within those studies prevent us from conducting a robust meta‐analysis. However, studies that supported the efficacy of revegetation reported IPS cover or biomass to be reduced 11%–94% by revegetation (Blumenthal, Jordan, & Svenson, ; Herron, Jonas, Meiman, & Paschke, ). Although it is important to consider these responses within the context of potential positive‐outcome publication bias (Fanelli, ), this wide range emphasizes that the results of restoration efforts may be context dependent and that there is a need to identify which conditions maximize the ability of revegetation to suppress IPS.…”
Section: Revegetation To Suppress Invasion: Evidencementioning
confidence: 99%
“…The small number of studies we identified and the diverse methods and metrics used within those studies prevent us from conducting a robust meta-analysis. However, studies that supported the efficacy of revegetation reported IPS cover or biomass to be reduced 11%-94% by revegetation (Blumenthal, Jordan, & Svenson, 2003;Herron, Jonas, Meiman, & Paschke, 2013).…”
Section: Re Veg E Tati On To Suppre Ss Inva S Ion: E Viden Cementioning
confidence: 99%
“…Also, they may decrease growth and reproduction of invasive annual grasses via competitive interactions. An effective, integrated restoration approach for improving establishment of native species involves seeding nonnative annuals such as common wheat (Triticum aestivum) that can serve as cover crops and reduce success of non-native invasive annuals in the first year, and then seeding native species in the following year (Koscelny et al 1990, Monaco et al 2003, Herron et al 2013. Because species like common wheat are typically sterile, competition from these species in the second year and the risk that they will reproduce and become invasive is nil.…”
Section: Introductionmentioning
confidence: 99%